A Wonderful Ramadan at UMP with RM130,000 contribution by Etiqa - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) received a sum of RM130,000 from Etiqa, the insurance and takaful business of Maybank, which would bring joys and cheers to many of the undergraduates and the needy in the holy month of Ramadan.